Biogeografia do gênero Triatoma Laporte, 1832 (Hemiptera, Reduviidae, Triatominae): distribuição, padrões de riqueza, endemismo, e diversificação - Leite, Gustavo Rocha (2013)
The genus Triatoma Laporte, 1832 groups species responsible for transmitting Trypanosoma cruzi. From 82 described species, 73 occur in the Americas, seven in Asia and Oceania, one is pantropical, and one represents a fossil record from Dominican Republic. In this study, by means of a detailed and exhaustive bibliographic review, we compiled occurrence records of the Triatoma species to obtain high resolution and updated distribution maps of each species, with help of distribution modeling (MAXENT). We then seek for biogeographical patterns of Triatoma by means of panbiogeography tools, in order to recognize primary homologies and confront them to phylogenetic hypothesis for the genus. The identification of diversification areas helps in the reconstruction of the group history, and based in its results, we discussed on the history, origin, evolution, diversification, and species grouping. We present up to date distribution maps, a brief description of each species, containing the most important and present-day distributional, ecological, epidemiological, and taxonomic aspects. For the panbiogeography analysis, we submitted the data to a geometric and parsimony track analysis, and a parsimony analysis of endemicity, in a multiscale approach (1–6º). We analyzed the biogeographical hypothesis together with phylogenies proposed for the group, to infer diversification areas and cladogenesis events. Nine generalized tracks and five endemism areas were identified and associated to geological events and to the history of the group. The most probable and consistent identified diversification areas are located: (1) in south-central Mexico (Rubrofasciata group); (2) in the extreme northwest of South America, following the South America transition zone in its initial portion (northern of the Andes) in Colômbia and Ecuador (Dispar group); (3) in the meridional and south-central of the Andes, north of Argentina (Infestans group); and (4) in the northeast of Brazil, including Caatinga and Cerrado biomes (Infestans group). We discussed the grouping of some species and, for the first time for the group, we presented the most probable and consistent diversification areas of the genus Triatoma, the potential relationships between these areas and historical events, as well as the indication of possible areas for the group origin. Future work should priories more complete and well solved phylogenetic reconstructions of the group, integrating molecular and morphological data